The Effect of Effleurage along with Moisturizing Application on Skin Elasticity - Afrianti Wahyu Widiarti; Dwi Kurniawati (RSUP Dr. Kariadi, 2023)
Background: A decrease in skin elasticity is a problem often complained of, especially by women. Changes in some of the structure and elasticity of the skin occur with age as a result of reduced production of natural oils and skin collagen. There are several ways to increase skin elasticity, including by stimulating collagen. One of them is by using topical skin care such as using a moisturizer that suits skin type. Aim: This study intends to determine the effect of effleurage in the application of moisturizer on skin elasticity. Method: The research design was a randomized controlled-trial with two groups pre and posttests conducted on 30 students of the Physiotherapy Department Surakarta randomly selected and divided into two groups. The treatment group applied moisturizer to the skin using the effleurage technique, while the control group applied only moisturizer. The groups were intervened for two weeks. Skin elasticity was measured using the EH-900U skin analysis system. Result: The Pre-Posttests of group one’s skin elasticity with the Paired Samples T-Test yielded a p value = 0.013, which means that there is an effect of effleurage in applying moisturizer on skin elasticity. The Pre-Posttests of group two's skin elasticity with the Wilcoxon Test yielded a p value = 0.551, which means that there is no effect of topical moisturizer on skin elasticity. There were significant differences in the treatment and control groups Conclusion: The application of moisturizer along with effleurage for skin elasticity is more robust than applying only topical moisturizer.